Is it possible to predict improved diabetes outcomes following diabetes self-management education: a mixed-methods longitudinal design. Issue 11 (2nd November 2015) - Huxley, Caroline; Sturt, Jackie; Dale, Jeremy; Walker, Rosie; Caramlau, Isabela; O'Hare, Joseph P; Griffiths, Frances
Abstract : Objective: To predict the diabetes-related outcomes of people undertaking a type 2 Diabetes Self-Management Education (DSME) programme from their baseline data. Design: A mixed-methods longitudinal experimental study. 6 practice nurses and 2 clinical academics undertook blind assessments of all baseline and process data to predict clinical, behavioural and psychological outcomes at 6 months post-DSME programme. Setting: Primary care. Participants: –31 people with type 2 diabetes who had not previously undertaken DSME. Intervention: All participants undertook the Diabetes Manual 1:1 self-directed learning 12-week DSME programme supported by practice nurses trained as Diabetes Manual facilitators. Outcome variables: Glycated haemoglobin (HbA1c), diabetes knowledge, physical activity, waist circumference, self-efficacy, diabetes distress, anxiety, depression, demographics, change talk and treatment satisfaction. These variables were chosen because they are known to influence self-management behaviour or to have been influenced by a DSME programme in empirical evidence. Results: Baseline and 6-month follow-up data were available for 27 participants of which 13 (48%) were male, 22 (82%) white British, mean age 59 years and mean duration of type 2 diabetes 9.1 years. Significant reductions were found in HbA1c t(26)=2.35, p=0.03, and diabetes distress t(26)=2.30, p=0.03, and a significant increase in knowledge t(26)=−2.06, p=0.05 between baseline and 6 months. No significant changes were found in waist circumference, physical activity, anxiety, depression or self-efficacy. Accuracy of predictions varied little between clinical academics and practice nurses but greatly between outcome (0–100%). The median and mode accuracy of predicted outcome was 66.67%. Accuracy of prediction for the key outcome of HbA1c was 44.44%. Diabetes distress had the highest prediction accuracy (81.48%). Conclusions: Clinicians in this small study were unable to identify individuals likely to achieve improvement in outcomes from DSME. DSME should be promoted to all patients with diabetes according to guidelines.